Online monitoring of cold metal transfer (CMT) process using infrared thermography. Issue 1 (2nd January 2017) - Thomas, K. Renil; Unnikrishnakurup, Sreedhar; Nithin, P. V.; Balasubramaniam, Krishnan; Rajagopal, Prabhu; Prabhakar, K. V. Phani; Padmanabham, G.; Riedel, Frank; Puschmann, Markus
Abstract: Online (passive) thermographic inspection of overlap joints of aluminium and zinc coated steel sheets made by cold metal transfer weld brazing process was explored. Different experimental trials were conducted for demonstrating the feasibility of thermographic inspection to detect the porosities, improper weld bead and to differentiate the pre weld temperature. The whole process was monitored using infrared cameras in different wavelength region. Image analysis algorithms were developed to reconstruct the thermal images that contain the signatures of the weld defects and to extract the pre weld temperature and its evolution with distance from the centre of the weld torch. Post-weld radiography lends strong support to the observations.